(untitled) (Journal of Applied Learning and Teaching, 2019)
For the functions of enhancing students’ learning performance by integrating advanced technologies and equipment, the smart classroom has become a worldwide research issue recently. This study aims to produce a model to determine what variables affect students’ interaction in a smart learning environment. Participants consist of 254 undergraduate students and master students who have experience of learning in a smart classroom for more than one semester. Two scales were adopted in this study as a data instrument. The first one is the “Smart Classroom Inventory”. The second one is “Interaction and Student Satisfaction Scales”. The Structural Equation Model (SEM) was used in this study for data analysis. A model is built to explain the relations between students’ interaction and variables related to the smart classroom. According to the research results, we find that students’ interaction can be positively affected by variables of Spatial physical design, Learning data, Differentiation, and Cooperation related to the smart classroom.